-4(-x-1)=3x+1

Simple and best practice solution for -4(-x-1)=3x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-x-1)=3x+1 equation:



-4(-x-1)=3x+1
We move all terms to the left:
-4(-x-1)-(3x+1)=0
We add all the numbers together, and all the variables
-4(-1x-1)-(3x+1)=0
We multiply parentheses
4x-(3x+1)+4=0
We get rid of parentheses
4x-3x-1+4=0
We add all the numbers together, and all the variables
x+3=0
We move all terms containing x to the left, all other terms to the right
x=-3

See similar equations:

| -1=5/3-1/6x | | 10x+42=-38 | | 3/4x=9/7 | | x+6=2/3 | | 7m=40/3 | | x^2+3x-70=0x2+3x−70=0 | | -10h/27=2/9 | | 8(4x-6)=4(7x-3) | | 10-(2x+5)=3x+3/4 | | x4+7=14 | | 6x+6(6x+x+6x)-3=10 | | 20x−17x=x+16 | | 15x-12x=2x+18 | | 4a+6=5a-4 | | 15x−12x=2x+18 | | 2x+x+36=180 | | 4x-2=-3x-9 | | 5(3w+9)/3=-1 | | 45=30/t | | 200-4x=100-0.5x | | X-3(4-x)=2 | | (49+39.99*x)=45.99*x | | 20=x/120 | | f(1)=3(1)-2 | | x+8=2-3 | | g/6=16 | | x5-8=-3 | | 3(h-10)+2=5 | | x/5-4=17 | | 5y+24=52 | | 9(c-86)=72 | | t^2*50t=0 |

Equations solver categories